Multilevel strategic planning in the system of institutional governance mechanisms in Ukraine - Melnyk, Alla (Herald of Economics, 2020)
Introduction. The dilemma of «chaos» (a free choice of behavior by each subject) or development based on assessments and strategic goals, formed in account with internal and external factors that would allow keeping things organised, persists in countries that shape a new economic model. Dismantling of the old economic system, the formation  of the foundations of post-industrial development in the XXI century raise the issue of strategic planning.Purpose. The study is devoted to the development of the methodological framework of strategic planning based on clarifying the relationships, goals, differences of its main components in the multilevel management system. Besides, it aims to assess the current practices of strategic planning tools in Ukraine and identify areas for improvement in the context of synergy and its security development.Methods. The methodological basis of the study is the use of systematic and comparative approaches in the analysis of the theory and practice of strategic planning at different levels of government. The following research methods were used: induction and deduction; system analysis is used to identify the components of strategic planning at different levels of management; PEST analysis is used to identify factors leading to insufficient effectiveness of this tool in a multilevel management system; institutional and comparative analysis is used to clarify goals and differences of individual components of the system of strategic planning; abstract and logical is used to identify patterns of evolution of strategic planning in the future; marketing analysis is used to clarify the content of management activities in the framework of strategy.Results. Scientific approaches to the interpretation of the essence and place of strategic planning in the management system are generalized. The author’s position on clarification of the content of strategic planning, delimitation of the concepts of «strategy» (as a direction of action), «strategic planning» (as a management function) is presented. The peculiarities of the presentation of strategic planning at different levels of the management hierarchy in Ukraine are shown.The reasons for the low efficiency of strategic goals success in the course of realization of strategies and strategic plans in domestic practice are revealed. The place of strategic planning in the system of institutional mechanisms of multilevel management is specified considering its current documents in Ukraine; the goals and differences of functional load at different levels of the management hierarchy are differentiated.The empirical analysis of the practice of strategic planning allowed us to identify the main challenges that require the search for management decisions at the methodological, legal, and administrative levels. Specifically, the problem of systematization, hierarchy, and autonomy of planning documents; inconsistency of government’s long-term and medium- term strategies with current financial documents (budgets); low quality of macroeconomic forecasts and disregard for international strategies, the presence of «institutional traps» have been defined.Ways to improve strategic planning at the regional and local levels have been identified, in particular in connection with the decentralization reform and increasing the power of local self-government. Attention is paid to ensuring methodologically sound and procedurally fixed interrelation of planning documents, program and financial documents, organizational and methodological support of monitoring and evaluation, as well as information feedback, application of regional and local marketing tools, etc.The conclusion is made about the expediency of considering strategic planning in the system of management mechanisms in the country as a multilevel system, increasing the level of its systematization to achieve a synergy effect, practical implementation of the highest level of strategic planning - strategizing.Discussion. In the mentioned context, the prospects for further research are the problems of coordination of strategic and financial-budget planning systems, the formation of strategic plans in a new format of administrative-territorial entities, the development of methodological and applied provisions for the implementation of strategies.